A FEW NOTES ON THE EVOLUTION OF THE COMMERCIAL SALES CONTRACT REGULATION - Dan VELICU (Challenges of the Knowledge Society, 2015)
Today, we think that the commercial sales has a long history as institution and therefore the relocation of its regulation from the commercial code to the civil code seems to be an authentic revolution inside the European or national private law. In fact, the modern regulation of commercial sales emerged only in the nineteenth century and a proper regulation was strengthened in that very century. The present paper aims to analyze if this kind of revolution is an useful and necessary and if, by relocation, the institution has really disappeared.